RETRACTED: Natural radioactivity of forest landscape soils - Kramareva Tatiana; Gorbunova Nadezhda; Gromovik Arkady; Lyubashevsky Dmitry; Kulikova Elena (E3S Web of Conferences, 2023)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001